(untitled) (Journal of Pharmaceutical Negative Results, 2022)
We aimed to assess the prognosis on the onset of arthritis in the diabetic patient after severe SARS-CoV-2 infection.Methods: The medical data of 10 patients with type 2 diabetes melitus, obese or overweight, hospitalized, in the interval between 1st of February and 31st of July 2021 at ``Saint Spyridon`` County Hospital Iasi, Romania for SARS-Cov-2 infection with were analyzed.Results: Although all the patients received treatment with tocilizumab 8 mg/kg body during 30 days, the blood analysis showed very high level of interleukins 6, and the joint painful symptoms continued to be manifested. The interleukins 6 serum level is higher and persistent in diabetic patient with SARS-CoV-2 infection, against the background of pre-existing chronic inflammation induced by diabetes, obesity and the glycemic imbalance. This renders the cytokine release syndrome difficult to control in the diabetic patients with severe infections, which leads to a higher hazard of interleukin 6 transcription errors. SARS-CoV-2 diabetic patients run the risk of developing long-term arthritis due to the uncontrolled, permanent synthesis of this cytokine.Conclusion: The immunologic modifications associated with the severe coronavirus infection acting on the predisposing genetic background (HLA-DR4/DR1), might underlie the onset of the arthritis on the long-term due to the exaggerated activation of IL-6 and the chronicity of the inflammation it generates. Studies shall be required that monitor on the long-term the diabetic patients surviving a severe Sars-CoV-2 infection as to the occurrence of the arthritis.